The Effect of Work Engagement and Self-Efficacy on Job Burnout of Credit Analyst - Ni Nyoman Sri Rahayu Damayanti (International Journal of Applied Business and International Management, 2019)
The purpose of this research is to determine the effect of work engagement and self-efficacy on credit analyst’s job burnout. Job burnout is one aspect that influence negligence in analyze a credit application. Job burnout is a condition with emotional fatigue, physical fatigue, and lack of energy which can cause a person's low performance. BRI is the largest profit bank in Indonesian banking industry and always grows up to 2017. High number of debtors and credit applications can also increase the workload and job burnout for the analyst. Job burnout can be minimized by a high work engagement between workers and their job. Work engagement is a condition when worker easier to manage work relationship and manage stress on work pressure. Selfefficacy also will prevent job burnout. Person with high self-efficacy has a good competence to face challenges in their workplace. This study used primary data source collected by questionnaire technique. Respondents in this study were credit analysts at Bank Rakyat Indonesia Renon Branch Office. Hypothesis was tested by using multiple linear regression analysis. The result showed that work engagement and self-efficacy had a negative and significant effect on job burnout of credit analyst.